From captive to convert - Ridley, Yvonne; One Islam Publications (N.S.W, Australia : One Islam Productions, 2006)
Be inspired, as Yvonne Ridley, a passionate British journalist, describes the story of how she was held captive by Taliban soldiers in Afghanistan. Intimidated by their presence, she persisted with great fighting zeal to return home to her awaiting family. sit with her in interoccations, war torn Afghan jail facilities and then shed tears of sorrow and joy as thing touching story unfolds. Join her as she challenges Taliban soldiers and falsely labeled'Terrorist'; only to later fall in love with their character, morality, respect and way of life
Title from title screen
Presenter : Yvonne Ridley
Keywords: Afghanistan -- History -- 1989-2001; Islam